Comparison between Allopurinol and Febuxostat in management of gout patients - a prospective study (Bangladesh Journal of Medical Science, 2012)
Aim:To assesses the efficacy of a relatively new drug-Febuxostat in management of gout and its comparison with allopurinol. Method: A comparative study of both Allopurinol and Febuxostat was done on 100 patients of gout. Both were studied for efficacy. side effects and for gout flare up. Results: Primary efficacy end point (baseline values) - a serum urate concentration of less than 6.0mg per deciliter at the last three measurements was reached by 54 %( 27/50) of group A patients taking 80mgs of febuxostat and 25 %( 12/50) of group B patients taking allopurinol 300mgs per day (P